1951
DOI: 10.1021/ac60053a018
|View full text |Cite
|
Sign up to set email alerts
|

Alphazurine G and Some N,N'-Substituted Benzidines as Redox Indicators

Abstract: The purpose of this study was to investigate the usefulness of a typical triarylmethane dyestuff as a redox indicator.The dye chosen for this purpose was Alphazurine G, C.I. No. 712, which had already

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1959
1959
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, recent laboratory measurements of the dissociative electron recombination of N 2 H + reveal that the dominant channel results in cleavage of the N-N bond (Geppert et al 2004), in contrast to previous measurements that indicated that this channel was unimportant (e.g. Adams et al 1991). This new mechanism provides a means to break apart N 2 at a faster rate than He + attack and may lead to large 15 N enhancements on the proton-transfer timescale of ∼10 5 yr.…”
Section: Introductionmentioning
confidence: 83%
“…However, recent laboratory measurements of the dissociative electron recombination of N 2 H + reveal that the dominant channel results in cleavage of the N-N bond (Geppert et al 2004), in contrast to previous measurements that indicated that this channel was unimportant (e.g. Adams et al 1991). This new mechanism provides a means to break apart N 2 at a faster rate than He + attack and may lead to large 15 N enhancements on the proton-transfer timescale of ∼10 5 yr.…”
Section: Introductionmentioning
confidence: 83%
“…In this Letter, we are motivated to revisit our previous models as a result of several recent discoveries. First, the experimental results of Geppert et al (2004) have been challenged by Molek et al (2007), who demonstrated that recombination of N 2 H + leads predominantly to N 2 + H, as indicated in previous work (Adams et al 1991). The new results indicate that rupture of the N 2 bond occurs rarely, if at all, with an upper limit for the NH + N 0 branching ratio of 5 per cent.…”
Section: Introductionmentioning
confidence: 93%
“…Good is 1) has reviewed the data available up to 1975. With the inception of the SIFT technique accurate temperature dependencies have been obtained for several ternary association reactions which indicates that the variation of the ternary rate coefficients with temperature closely conforms to a simple power law behaviour (k et T -n) as predicted by statistical theory, but with n much smaller than predicted [131][132][133]. Such data is contributing to a growing understanding of the mechanistic aspects of ion-molecule association reactions 134' 1as)…”
Section: Ternary Ion-molecule Reactionsmentioning
confidence: 71%